Molecular basis of APC/C regulation by the spindle assembly checkpoint - Alfieri, Claudio (Nature, 2016)
In the dividing eukaryotic cell the spindle assembly checkpoint (SAC) ensures each daughter cell inherits an identical set of chromosomes. The SAC coordinates the correct attachment of sister chromatid kinetochores to the mitotic spindle with activation of the anaphase-promoting complex/cyclosome (APC/C), the E3 ubiquitin ligase that initiates chromosome separation. In response to unattached kinetochores, the SAC generates the mitotic checkpoint complex (MCC), a multimeric assembly that inhibits the APC/C, delaying chromosome segregation. Here, using cryo-electron microscopy we determined the near-atomic resolution structure of an APC/C-MCC complex (APC/C(MCC)). We reveal how degron-like sequences of the MCC subunit BubR1 block degron recognition sites on Cdc20, the APC/C coactivator subunit (Cdc20(APC/C)) responsible for substrate interactions. BubR1 also obstructs binding of UbcH10 (APC/C’s initiating E2) to repress APC/C ubiquitination activity. Conformational variability of the complex allows for UbcH10 association, and we show from a structure of APC/C(MCC) in complex with UbcH10 how the Cdc20 subunit intrinsic to the MCC (Cdc20(MCC)) is ubiquitinated, a process that results in APC/C reactivation when the SAC is silenced.